An Analysis of Directive Speech Acts and Their Felicity Conditions in Jokowi’s G20 Session I Speech - Toisuta, Emanuela Giovanni; Aritonang, Parjolo (MATAI: International Journal of Language Education, 2024)
This study aims to find out the type of directive speech acts uttered by Jokowi in his speech at the 17th G20 Opening. Searle and Cook felicity condition, propositional content on warning, advice, and request are used for the analysis. The data collected from Jokowi’s opening speech to all the guest and attendees. The results revealed that propositional content on warning, advice, and request are the attempt of the speaker for the listeners to do the action. In order, propositional content is addressed to the listeners which are the Leaders concerning what they should do in the future. The speaker also believes that the listeners will meet his requirement in the preparatory condition. In sincerity condition, the speaker expects the speakers to listen to what he said since it will benefit all of them. Moreover, advice, order, and request are counted as the attempt of Jokowi to make others do what he said in essential condition. Whereas, warning is to prevent what could happen in the future. Thus, Jokowi’s speech clearly used directive speech act in informing his opinion.